Nuclear Actin Is Required for Transcription during Drosophila Oogenesis - Sokolova, Maria; Moore, Henna M.; Prajapati, Bina; Dopie, Joseph; Meriläinen, Leena; Honkanen, Mikko; Matos, Rita Cerejeira; Poukkula, Minna; Hietakangas, Ville; Vartiainen, Maria K. (iScience, 2018)
Actin has been linked to processes spanning the whole gene expression cascade, from regulating specific transcription factors, such as myocardin-related transcription factor, to chromatin remodeling and RNA polymerase function. However, whether actin controls the transcription of only specific genes or has a global role in gene expression has remained elusive. Our genome-wide analysis reveals, for the first time, that actin interacts with essentially all transcribed genes in Drosophila ovaries. Actin co-occupies the majority of gene promoters together with Pol II, and on highly expressed genes, these two proteins also associate with gene bodies. Mechanistically, actin is required for Pol II recruitment to gene bodies, and manipulation of nuclear transport factors for actin leads to the decreased expression of eggshell genes. Collectively, these results uncover a global role for actin in transcription and demonstrate the in vivo importance of balanced nucleocytoplasmic shuttling of actin in the transcriptional control of a developmental process.